Ibuprofen versus steroids: risk and benefit, efficacy and safety - M. Giovannini; M. Mandelli; C. Gualdi; S. Palazzo (PAGEPress Publications, 2013)
In the last few years we have observed an upward trend in the employment of ibuprofen as anti-inflammatory and antipyretic therapy. Therefore the pediatrician has often a precious option in the anti-inflammatory and antipyretic treatment in children instead of using steroids and paracetamol. In clinical practice ibuprofen can be used in the treatment of headache, toothache, otalgy, dysmenorrhea, neuralgia, arthralgia, myalgia, abdominal pain and fever: it is the first choice for these common diseases. However, the use of steroids is a routine, even if non-corticosteroid anti-inflammatory molecules could be useful. Certainly steroids are powerful anti-inflammatory, indicated for the treatment of chronic inflammatory disorders and in acute respiratory and allergic diseases. Beside, thanks to their chemical and pharmacological profile, they also provide patients with an antipyretic effect. However, the use of steroids must be reserved to cases in which other classical antipyretics such as non-steroidal anti-inflammatory drugs are not effective. The possible side effects and risks associated with stepping down steroids must be considered. Although "steroids-phobia" should be discouraged, steroids are to be reserved only as the first indication. In all other cases the pediatrician can use ibuprofen, whose efficacy and safety are widely demonstrated by now.